Desconsideração da personalidade jurídica - Clápis, Flávia Maria de Morais Geraigire (2006)
This dissertation approaches the aspects which involve the theory of inconsiderateness of the juridical personality, with the goal of tracing standards for its correct application. The constantly accentuated worry of the doctrine is how the theory of inconsiderateness of the juridical personality has been used by our Tribunals, so that it is not applied, indiscriminately, maintaining the principle of autonomy of the legal entity to, only in exceptional cases, disregard it. The autonomy of the legal entity is of major importance for the social-economical development, once it limits the responsibility of the one who wants to invest in the country. The introduction in the positive Brazilian law of the inconsiderateness by the Defense Code of the Consumer conferred prerogative to the theory of inconsiderateness which are strange to it and do not correspond with the oriented principles of the private law. The 50th Article of the Civil Code of 2002 represented an advance to guide the correct application of the theory, because it brought to the operators of the law the appropriate effectiveness, which before was difficult to be reached. It had the gift to do it in a correct and disciplinary way, establishing adequate standards with its juridical basis and, with this, the opportunity to promote new tendencies to the theory of inconsiderateness, observing the principles which guide it, without leaving out the correct importance to the social and economical interests. The theories of inconsiderateness developed by the people who doctrine had the goal to systematize the theme, prevailing in our juridical ordination the subjective conception, through which it is only possible to remove the principle of autonomy of the legal entity in exceptional cases, ever since it is confirmed the fraud or abuse of right, being demanded a guilty behavior of the agent. Such principle should be joined to the character in a subsidiary way, necessary of the correct framing of the theory. There are divergences concerning the application of the theory of inconsiderateness of the juridical personality on the various areas of the law, for some branches of our ordination contemplate in a wrong way the inconsiderateness, when the correct treatment would be the direct imputation of the responsibility of the partners and administrators, since within the personal responsibility it does not exist the manipulation of the juridical personality, but only the characterization of the illicit way concerning the particular acts. The inconsiderateness of the juridical personality is the adequate way to repress the abuses perpetrated, by society, or by group of companies. If correctly applied, improves the institute of the legal entity. However, the worry is that the institute is not applied without any standard, what will give an opportunity to the discredit of the legal entity, leading to social and economic losses